Domestic and Foreign Earnings, Stock Return Variability, and the Impact of Investor Sophistication - SEGAL, Dan (Institutional Knowledge at Singapore Management University, 2005)
We examine the importance of foreign earnings relative to domestic earnings for a sample of U.S. multinationals using variance decomposition. Our methodology represents an alternative and complementary approach over the prior literature, which is based on traditional regressions and earnings response coefficients. We document that domestic earnings are more important in explaining the variance of unexpected returns than are foreign earnings and that the relative importance of domestic earnings is a decreasing function of investor sophistication. Last, we classify institutional investors as either short- or long-term oriented following Bushee [1998]. We find that the variance contribution of foreign earnings increases with the level of investment by long-term investors. In contrast, there is no significant relation between the degree of ownership by short-term (or transient) investors and the variance contribution of domestic and foreign earnings. Overall, our results are consistent with Thomas's [1999] finding that investors on average underestimate the persistence of foreign earnings.